Glass as well as preparation method and application thereof
By etching the acute angle-inclined convex structure on the side of the arc surface on the glass body, the problem of mechanical properties degradation caused by stress concentration in the existing glass preparation process is solved, and the effect of excellent mechanical properties of glass and low preparation cost is achieved.
Patent Information
- Application Number
- CN202410156715.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-02
- Publication Date
- 2025-04-15
AI Technical Summary
In the existing glass preparation process, there is a stress concentration area on the surface of the frosted liquid, which leads to a decrease in the mechanical properties of the glass and a decrease in the good rate.
Using a novel glass preparation method, by etching a plurality of convex structures on the glass body, the sides of the convex structure are arc surfaces, and the angle between the first sub-surface and the side surface is an acute angle to reduce the stress concentration area.
The mechanical properties of glass, including bending strength and impact resistance, enhance the overall strength and texture diversity of glass, and reduce the preparation cost.
Smart Images

Figure CN119822644A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of glass materials, and in particular to glass and its preparation method and application. Background Art
[0002] At present, glass can be processed on the surface to obtain a variety of glass with different textures due to its hardness and good chemical stability, and is used in a variety of equipment and occasions. In the related art, the preparation of textured glass using frosting liquid, although the prepared glass surface has different textures, there are a large number of stress concentration areas on the glass surface, which will cause a significant decrease in the mechanical properties of the glass and a decrease in the good rate. Therefore, it is necessary to further optimize the preparation process of glass to obtain glass with excellent mechanical properties. Summary of the invention
[0003] In view of this, the present application provides a glass and a preparation method and application thereof. The preparation method is novel, the process is simple, the preparation cost is low, and the prepared glass has excellent mechanical properties, which is conducive to the wide application of glass.
[0004] In a first aspect, the present application provides a glass comprising a first glass body and a plurality of raised structures arranged on a first sub-surface of the first glass body, wherein the raised structures have a side surface, the side surface is a curved surface, and an angle between the first sub-surface and the side surface is an acute angle.
[0005] Optionally, the acute angle is 50°-80°.
[0006] Optionally, the orthographic projection area of the protruding structure on the first sub-surface accounts for 70%-80% of the area of the first sub-surface.
[0007] Optionally, the curvature of the side surface is 2m -1 -5m -1 .
[0008] Optionally, the lateral dimension of the protruding structure is 0.1 mm-2.5 mm, the width of the protruding structure is 0.1 mm-1.5 mm, the height of the protruding structure is 0.1 μm-30 μm, and the spacing between adjacent protruding structures is 0.1 mm-0.2 mm.
[0009] Optionally, the lateral dimension of the protruding structure is 0.1 mm-1 mm, the width of the protruding structure is 0.1 mm-1 mm, the height of the protruding structure is 5 μm-15 μm, and the spacing between adjacent protruding structures is 0.1 mm-0.2 mm.
[0010] Optionally, the lateral dimension of the protruding structure is 1 mm-2.5 mm, the width of the protruding structure is 0.5 mm-1.0 mm, the height of the protruding structure is 10 μm-30 μm, and the spacing between adjacent protruding structures is 0.1 mm-0.13 mm.
[0011] Optionally, the haze of the glass is 40%-55%.
[0012] Optionally, the visible light transmittance of the glass is 60%-70%.
[0013] Optionally, the surface roughness of the glass is 0.1 μm-0.3 μm.
[0014] Optionally, the bending strength of the glass is greater than or equal to 430N.
[0015] Optionally, the glass has an impact resistance height greater than or equal to 45 cm when impacted by a steel ball with a mass of 65 g.
[0016] The glass provided in this application has excellent mechanical properties and good comprehensive performance.
[0017] In a second aspect, the present application also provides a method for preparing glass, comprising:
[0018] Providing a glass body, wherein the glass body has a first surface and a second surface arranged opposite to each other, and the first surface has a first area and a second area;
[0019] After the first area is etched for the first time, the first area and the second area are etched for the second time to obtain glass; the glass includes a first glass body and a plurality of protruding structures arranged on a first sub-surface of the first glass body, the protruding structures have a side surface, the side surface is a curved surface, and the angle between the first sub-surface and the side surface is an acute angle.
[0020] Optionally, the first etching is performed using a first etching solution, wherein the first etching solution includes hydrofluoric acid.
[0021] Optionally, the concentration of the hydrofluoric acid in the first etching solution is 1%-5%.
[0022] Optionally, the first etching time is 5 min-10 min.
[0023] Optionally, the second etching is performed using a second etching solution, wherein the second etching solution includes at least one of ammonium salt, fluoride, fluorosilicate and inorganic acid.
[0024] Optionally, the ammonium salt includes at least one of ammonium fluoride, ammonium bifluoride and ammonium chloride.
[0025] Optionally, the fluoride includes at least one of sodium fluoride, potassium fluoride and calcium fluoride.
[0026] Optionally, the fluorosilicate includes at least one of sodium fluorosilicate and potassium fluorosilicate.
[0027] Optionally, the inorganic acid includes at least one of nitric acid, hydrochloric acid, sulfuric acid and hydrofluoric acid.
[0028] Optionally, before performing the first etching, the method further includes: disposing a photoresist layer on the first surface, and exposing and developing the photoresist layer to expose the first region.
[0029] Optionally, the thickness of the photoresist layer is 3 μm-6 μm.
[0030] Optionally, the exposure energy is 600 mj / cm 2 -1000mj / cm 2 .
[0031] Optionally, a developer is used for the development, and the developer includes at least one of a potassium hydroxide solution and a sodium hydroxide solution, and the concentration of the developer is 0.8%-1.2%.
[0032] Optionally, the development time is 1 min-2 min.
[0033] Optionally, providing the glass body includes: performing heat bending treatment on a glass precursor to obtain the glass body with a curved surface.
[0034] The glass preparation method provided in the present application is novel, has a simple process, and has a low preparation cost. The prepared glass has excellent mechanical properties, which is conducive to the wide application of glass.
[0035] In a third aspect, the present application further provides a glass cover plate, wherein the glass cover plate comprises the glass described in the first aspect or the glass produced by the preparation method described in the second aspect.
[0036] Optionally, the glass cover plate further includes a decorative layer, and the decorative layer is arranged on the surface of the glass.
[0037] The glass cover provided in the present application has high strength and excellent drop resistance, which is conducive to the wide application of glass cover plates.
[0038] In a fourth aspect, the present application provides an electronic device, comprising the glass cover plate described in the third aspect.
[0039] The electronic device provided by the present application has a variety of appearances, thereby increasing the service life of the electronic device. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the embodiments or the prior art description. The specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.
[0041] Figure 1 A schematic cross-sectional view of glass provided in accordance with one embodiment of the present application.
[0042] Figure 2 A schematic top view of glass provided in accordance with one embodiment of the present application.
[0043] Figure 3 A flow chart of a method for preparing glass provided in one embodiment of the present application.
[0044] Figure 4 A schematic cross-sectional view of a glass body provided in accordance with one embodiment of the present application.
[0045] Figure 5 A schematic cross-sectional view of a glass substrate provided in one embodiment of the present application.
[0046] Figure 6 A schematic cross-sectional view of a glass body provided in another embodiment of the present application.
[0047] Figure 7 A flow chart of a method for preparing glass provided in another embodiment of the present application.
[0048] Figure 8 A flow chart of a method for preparing glass provided in yet another embodiment of the present application.
[0049] Fig. 9 A cross-sectional schematic diagram of a glass cover provided in one embodiment of the present application.
[0050] Fig.10 This is a surface morphology image of the glass substrate prepared in Example 1 of the present application, magnified 20 times.
[0051] Fig.11 This is a surface morphology image of the glass substrate prepared in Example 1 of the present application, magnified 5 times.
[0052] Fig.12 This is a surface morphology image of the glass substrate prepared in Example 1 of the present application, magnified 50 times.
[0053] Fig.13 This is a partial surface schematic diagram of the glass prepared in Example 1 of the present application.
[0054] Fig.14 This is a schematic diagram of a portion of the surface of the glass prepared in Example 2 of the present application.
[0055] Fig.15This is a schematic diagram of a portion of the surface of the glass prepared in Example 13 of the present application.
[0056] Fig.16 A partial surface schematic diagram of the glass prepared in Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0057] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0058] See also Figure 1 , is a cross-sectional schematic diagram of glass provided by an embodiment of the present application, wherein the glass 300 comprises a first glass body 31 and a plurality of protruding structures 33 arranged on a first sub-surface 32 of the first glass body 31, wherein the protruding structure 33 has a side surface, wherein the side surface is a curved surface, and the angle between the first sub-surface 32 and the side surface is an acute angle. Stress concentration refers to the phenomenon that stress increases significantly in a local area, which often occurs at sharp corners, holes, notches, and the like. There are no sharp corners in the protruding structure of the glass provided by the present application, and the side surface of the protruding structure is a curved surface, which reduces the stress concentration area when under pressure, avoids the pressure being concentrated at the connection between the side surface and the top surface of the protrusion when under pressure, and causes glass breakage, thereby improving the strength of the glass, and further facilitating the improvement of the mechanical properties of the glass; the angle between the first sub-surface and the side surface is an acute angle, which further reduces the stress concentration phenomenon and improves the strength of the glass; the plurality of protruding structures make the glass surface present a patterned texture and have a textured touch, enriching the visual effect of the glass and facilitating the use of the glass. The glass provided by the present application has excellent mechanical properties and fine texture, which is conducive to the wide application of glass.
[0059] In one embodiment of the present application, Figure 1 As shown, the acute angle α between the first sub-surface 32 of the first glass body 31 and the side of the protruding structure 33 is 50°-80°, and an appropriate acute angle can improve the mechanical properties of the glass. The acute angle α is the acute angle between the cut surface of the connecting line A between the side of the protruding structure 33 and the first sub-surface 32 on the first glass body 31 and the first sub-surface 32 of the glass. Specifically, the acute angle α between the first sub-surface of the first glass body and the protruding structure can be, but not limited to, 50°, 55°, 60°, 65°, 70°, 75° or 80°, etc. In one embodiment of the present application, the acute angle α between the first sub-surface of the first glass body and the protruding structure can be 50°-75°. In another embodiment of the application, the acute angle α between the first sub-surface of the first glass body and the protruding structure can be 60°-70°, which can further improve the mechanical properties of the glass.
[0060] In one embodiment of the present application, the curvature of the side surface of the protruding structure is 2m -1 -5m -1 The appropriate side curvature can avoid the formation of stress concentration areas on the sides of the protruding structure, which is beneficial to improving the mechanical properties of the glass. Specifically, the curvature of the curved surface can be, but is not limited to, 2 m -1 , 2.2m -1 、2.4m -1 、2.8m -1 、3m -1 、3.5m -1 、4m -1 、4.5m -1 or 5m -1 In one embodiment of the present application, the curvature of the arc surface can be 2m -1 -4m -1 In another embodiment of the present application, the curvature of the arc surface can be 3.5m -1 -5m -1 .
[0061] In one embodiment of the present application, the lateral dimension of the raised structure is 0.1 mm-2.5 mm. The maximum distance between any two points on the orthographic projection contour line of the raised structure on the first sub-surface is the lateral dimension of the raised structure. Specifically, the lateral dimension of the raised structure can be, but is limited to, 0.1 mm, 0.5 mm, 1 mm, 1.5 mm, 2 mm or 2.5 mm. In one embodiment of the present application, the lateral dimension of the raised structure can be 0.1 mm-1 mm. In another embodiment of the present application, the lateral dimension of the raised structure can be 1 mm-2.5 mm.
[0062] In one embodiment of the present application, the width of the protrusion structure is 0.1 mm-1.5 mm. Figure 2, is a top view schematic diagram of the glass provided in one embodiment of the present application, the distance between the two points a1 and a2 on the orthographic projection contour line of the convex structure 33 on the first sub-surface 32 is the largest, then the distance between a1 and a2 is the lateral dimension of the convex structure 33, the maximum distance between any two points of the convex structure 33 on the orthographic projection contour line on the first sub-surface 32 that are perpendicular to the line connecting a1 and a2 is the width of the convex structure 33, that is, the line connecting the orthographic projection contour lines b1 and b2 of the convex structure 33 on the first sub-surface 32 is perpendicular to the line connecting a1 and a2, and the distance between b1 and b2 is the largest among any two points on the orthographic projection contour line that are perpendicular to the line connecting a1 and a2, and the distance between b1 and b2 is the width of the convex structure 33. Specifically, the width of the convex structure may be, but is not limited to, 0.1 mm, 0.2 mm, 0.4 mm, 0.8 mm, 1 mm, 1.2 mm, 1.4 mm or 1.5 mm. In one embodiment of the present application, the width of the convex structure may be 0.1 mm-0.9 mm. In another embodiment of the present application, the width of the protrusion structure may be 0.8 mm-1.5 mm.
[0063] In one embodiment of the present application, the height of the raised structure is 0.1 μm-30 μm. The height of the raised structure is the maximum distance between the highest point of the raised structure and the first sub-surface. Specifically, the height of the raised structure may be, but is not limited to, 0.1 μm, 1 μm, 2 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm or 30 μm, etc. In one embodiment of the present application, the height of the raised structure may be 0.1 μm-15 μm. In another embodiment of the present application, the height of the raised structure may be 8 μm-30 μm.
[0064] In one embodiment of the present application, the spacing between adjacent protrusion structures is 0.1mm-0.2mm. The spacing between adjacent protrusion structures is the minimum distance between adjacent protrusion structures. Specifically, the spacing between adjacent protrusion structures may be, but is not limited to, 0.1mm, 0.12mm, 0.14mm, 0.16mm, 0.18mm or 0.2mm, etc. In one embodiment of the present application, the spacing between the protrusion structures may be 0.1mm-0.2mm. In another embodiment of the present application, the spacing between the protrusion structures may be 0.1mm-0.13mm.
[0065] In one embodiment of the present application, when the lateral dimension of the raised structure is 0.1mm-1mm, the width of the raised structure is 0.1mm-1mm, the height of the raised structure is 5μm-15μm, and the spacing between adjacent raised structures is 0.1mm-0.2mm, the glass surface presents a leather texture.
[0066] In one embodiment of the present application, when the lateral dimension of the raised structure is 1mm-2.5mm, the width of the raised structure is 0.5mm-1.0mm, the height of the raised structure is 10μm-30μm, and the spacing between adjacent raised structures is 0.1mm-0.13mm, the glass surface appears as water ripples.
[0067] In one embodiment of the present application, the outer surface of the raised structure includes at least one side. In some embodiments, the outer surface of the raised structure is composed of side surfaces. Specifically, the outer surface of the raised structure may be composed of one side surface, or may be composed of multiple side surfaces connected together. In some embodiments, the outer surface of the raised structure also includes the top surface of the raised structure, and the outer surface of the raised structure is composed of the top surface of the raised structure and the side surface of the raised structure, and the top surface of the raised structure and the side surface of the raised structure are connected by arcs. For example, the outer surface of the raised structure includes a top surface of a raised structure and at least one side surface of the raised structure, and the side surfaces of multiple raised structures are connected to the top surface of the raised structure by multiple arcs.
[0068] In one embodiment of the present application, the orthographic projection area of the convex structure on the first sub-surface accounts for 70%-80% of the area of the first sub-surface, and the distribution of the appropriate amount of convex structures reduces the stress concentration area, which can improve the bending resistance and impact resistance of the glass. Specifically, the orthographic projection area of the convex structure on the first sub-surface may be, but not limited to, 70%, 72%, 74%, 75%, 76%, 78% or 80% of the area of the first sub-surface. In one embodiment of the present application, the orthographic projection area of the convex structure on the first sub-surface may account for 70%-76% of the area of the first sub-surface. In another embodiment of the present application, the orthographic projection area of the convex structure on the first sub-surface may account for 74%-80% of the area of the first sub-surface.
[0069] In one embodiment of the present application, the haze of the glass is 40%-55%, which can improve the clarity of the glass texture and obtain different visual effects. Specifically, the haze of the glass can be, but is not limited to, 40%, 42%, 44%, 48%, 50%, 52%, 54% or 55%. In one embodiment of the present application, the haze of the glass can be 40%-52%. In another embodiment of the present application, the haze of the glass can be 48%-55%.
[0070] In one embodiment of the present application, the visible light transmittance of the glass is 60%-70%. Specifically, the visible light transmittance of the glass may be, but is not limited to, 60%, 62%, 64%, 66%, 67%, 68% or 70%. In one embodiment of the present application, the visible light transmittance of the glass may be 60%-67%. In another embodiment of the present application, the visible light transmittance of the glass is 64%-70%.
[0071] In one embodiment of the present application, the surface roughness of the glass is 0.1μm-0.3μm. The surface roughness of the glass is the surface roughness of the side surface with the raised structure. The appropriate roughness can improve the visual texture effect of the glass and the texture touch during use. Specifically, the surface roughness of the glass can be but is not limited to 0.1μm, 0.15μm, 0.18μm, 0.2μm, 0.25μm or 0.3μm, etc. In one embodiment of the present application, the roughness of the glass surface can be 0.1μm-0.22μm. In another embodiment of the present application, the roughness of the glass surface can be 0.2μm-0.3μm.
[0072] In one embodiment of the present application, the flexural strength of the glass is greater than or equal to 430N. Place the glass in a test fixture, set the upper wheelbase of the fixture to 18mm, the lower wheelbase to 36mm, the loading rod diameter to 6mm, apply pressure downward at a speed of 10mm / min until the product breaks, repeat the test 10 times, and the average value of the maximum applied pressure is the flexural strength. Specifically, the flexural strength of the glass may be, but is not limited to, greater than or equal to 430N, greater than or equal to 440N, greater than or equal to 450N, greater than or equal to 460N, greater than or equal to 470N, or greater than or equal to 480N, etc. In one embodiment of the present application, the flexural strength of the glass is greater than or equal to 455N. In another embodiment of the present application, the flexural strength of the glass is greater than or equal to 467N.
[0073] In one embodiment of the application, the impact resistance height of the glass under the impact of a steel ball with a mass of 65g is greater than or equal to 45cm. The glass is placed in a steel ball drop tester, using a 65g steel ball, and dropped from a height of 5cm, and the drop height is gradually increased (such as 10cm, 15cm, 20cm, 25cm, etc.) until the glass breaks and fails. Specifically, the impact resistance height under the impact of a steel ball with a mass of 65g can be, but is not limited to, greater than or equal to 45cm, greater than or equal to 50cm, greater than or equal to 55cm, greater than or equal to 57cm, greater than or equal to 60cm, greater than or equal to 65cm, or greater than or equal to 70cm, etc. In one embodiment of the present application, the impact resistance height under the impact of a steel ball with a mass of 65g can be greater than or equal to 55cm. In another embodiment of the present application, the impact resistance height under the impact of a steel ball with a mass of 65g can be greater than or equal to 65cm.
[0074] See also Figure 3 , is a flow chart of a method for preparing glass provided in one embodiment of the present application, comprising:
[0075] S101: providing a glass body, wherein the glass body has a first surface and a second surface arranged opposite to each other, and the first surface has a first area and a second area;
[0076] S102: After performing a first etching on the first area, performing a second etching on the first area and the second area to obtain glass; the glass includes a first glass body and a plurality of protruding structures arranged on a first sub-surface of the first glass body, the protruding structures have a side surface, the side surface is a curved surface, and an angle between the first sub-surface and the side surface is an acute angle.
[0077] The preparation method of glass provided by the present application is novel, simple in process, low in preparation cost, and can produce glass with fine texture and excellent mechanical properties. The first etching can etch the rough outline of the texture on the glass body, and the requirements for the texture fineness are low, thereby reducing the requirements for production equipment, and can be etched on curved or flat glass; the second etching is to etch fine textures, which can supplement the texture loss after the first etching, improve the good rate and texture fineness of the glass, and reduce the production cost. After the second etching, the side and top surface of the protrusion are eroded by the second etching liquid, resulting in the change of the shape of the side and top surface of the protrusion, and the horizontal side of the protrusion in the glass matrix becomes the arc side of the protrusion structure in the glass. There is no sharp corner in the protrusion structure, which reduces the stress concentration area when under pressure and reduces the stress concentration phenomenon when under force, which is beneficial to improve the mechanical properties of the glass and improve the three-dimensional sense of the glass texture; the angle between the first sub-surface and the side surface is an acute angle, which further reduces the stress concentration phenomenon and improves the strength of the glass.
[0078] In the present application, a first region of a first surface of a glass body is first etched to obtain a glass substrate. Figure 4 and Figure 5 , Figure 4 This is a cross-sectional schematic diagram of a glass body provided in one embodiment of the present application. Figure 5 This is a cross-sectional schematic diagram of a glass substrate provided by an embodiment of the present application, wherein a glass body 100 has a first surface 10 and a second surface 13 arranged opposite to each other, the first surface 10 of the glass body 100 has a first region 11 and a second region 12, and a glass substrate 200 is obtained after a first etching is performed on the first region 11 of the glass body 100, and the glass substrate 200 includes a second glass body 21 and a plurality of protrusions 23 arranged on a second sub-surface 22 of the second glass body 21; after a first etching is performed on the first region 11 of the glass body 100, a second sub-surface 22 is formed on the second glass body 21, and a portion of the glass body 100 that is not etched forms a protrusion 23 in the glass substrate 200, and a top surface 24 of the protrusion 23 is the first surface 10 of the glass body 100. After the first etching, the side surface of the protrusion 23 is a horizontal plane, and a rough outline of a texture is formed on the second sub-surface 22 of the glass substrate 200.
[0079] In one embodiment of the present application, the spacing between adjacent protrusions is greater than or equal to 30μm. The spacing between adjacent protrusions is large, and the first etching only needs to etch out the general outline of the texture, without the need to use ultra-fine equipment, reducing the requirements for production equipment and reducing preparation costs. Specifically, the spacing between adjacent protrusions may be, but is not limited to, greater than or equal to 30μm, greater than or equal to 32μm, greater than or equal to 34μm, greater than or equal to 38μm, greater than or equal to 40μm, or greater than or equal to 45μm, etc. In one embodiment of the present application, the spacing between adjacent protrusions may be greater than or equal to 32μm. In another embodiment of the present application, the spacing between adjacent protrusions may be greater than or equal to 40μm.
[0080] In one embodiment of the present application, the height of the protrusion is 5 μm-15 μm. Specifically, the height of the protrusion may be, but is not limited to, 5 μm, 8 μm, 9 μm, 10 μm, 13 μm or 15 μm. In one embodiment of the present application, the height of the protrusion may be 5 μm-12 μm. In another embodiment of the present application, the height of the protrusion may be 10 μm-15 μm.
[0081] In one embodiment of the present application, the lateral dimension of the protrusion is 0.05mm-10.5mm. The maximum distance between any two points on the orthographic projection contour line of the protrusion on the second sub-surface is the lateral dimension of the protrusion. Specifically, the lateral dimension of the protrusion can be, but is not limited to, 0.05mm, 0.1mm, 1mm, 2mm, 4mm, 6mm, 8mm or 10.5mm, etc. In one embodiment of the present application, the lateral dimension of the protrusion is 0.05mm-5mm. In another embodiment of the present application, the lateral dimension of the protrusion is 4.5mm-10.5mm.
[0082] In one embodiment of the present application, the width of the protrusion is 0.1mm-1mm. Consistent with the definition of width in glass, the distance between the two points a3 and a4 on the orthographic projection contour line of the protrusion on the second sub-surface in the glass substrate is the largest, then the distance between a3 and a4 is the lateral size of the protrusion, and the maximum distance between any two points on the orthographic projection contour line of the protrusion on the second sub-surface that are perpendicular to the line connecting a3 and a4 is the width of the protrusion, that is, the line connecting the orthographic projection contour lines b3 and b4 of the protrusion on the second sub-surface is perpendicular to the line connecting a3 and a4, and the distance between b3 and b4 is the largest among any two points on the orthographic projection contour line that are perpendicular to the line connecting a3 and a4, and the distance between b3 and b4 is the width of the protrusion. Specifically, the width of the protrusion can be, but is not limited to, 0.1mm, 0.2mm, 0.4mm, 0.6mm, 0.8mm, 0.9mm or 1mm, etc. In one embodiment of the present application, the width of the protrusion can be 0.1mm-0.6mm. In another embodiment of the present application, the width of the protrusion may be 0.5 mm-1 mm.
[0083] In one embodiment of the present application, a first etching solution is used for the first etching, and the first etching solution includes hydrofluoric acid, and the concentration (mass percentage) of hydrofluoric acid is 1%-10%, which can further improve the texture feel of the surface of the glass body. Specifically, the concentration of hydrofluoric acid can be but is not limited to 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8% or 10%. In one embodiment of the present application, the concentration of hydrofluoric acid can be 1%-3%, which can improve the fineness of the texture of the glass surface. In another embodiment of the present application, the concentration of hydrofluoric acid can be 2%-5%.
[0084] In one embodiment of the present application, the first etching solution includes at least one of nitric acid and sulfuric acid, and hydrofluoric acid. The addition of nitric acid and / or sulfuric acid can increase the dissociation constant of the first etching solution, increase the number of hydrogen ions in the first etching solution, and increase the etching strength of the first etching solution. In one embodiment of the present application, the mass percentage of nitric acid in the first etching solution is less than or equal to 0.5%, and the mass percentage of sulfuric acid is less than or equal to 0.5%, which can speed up the first etching. Specifically, in the first etching solution, the mass percentage of nitric acid can be but not limited to less than or equal to 0.1%, less than or equal to 0.2%, less than or equal to 0.3%, less than or equal to 0.4% or less than or equal to 0.5%, etc., and the mass percentage of sulfuric acid can be but not limited to less than or equal to 0.1%, less than or equal to 0.2%, less than or equal to 0.3%, less than or equal to 0.4% or less than or equal to 0.5%, etc. In one embodiment of the present application, the mass percentage of nitric acid can be less than or equal to 0.3%, and the mass percentage of sulfuric acid can be less than or equal to 0.2%. In another embodiment of the present application, the mass percentage of nitric acid may be less than or equal to 0.4%, and the mass percentage of sulfuric acid may be less than or equal to 0.25%.
[0085] In one embodiment of the present application, the first etching time is 1 min-10 min, which can obtain a rough texture profile while avoiding the adverse effects of long-term etching on the glass body. Specifically, the first etching time can be but is not limited to 1 min, 3 min, 5 min, 6 min, 7 min, 8 min, 9 min or 10 min. In one embodiment of the present application, the first etching time can be 5 min-8 min. In another embodiment of the present application, the first etching time can be 7 min-10 min.
[0086] In one embodiment of the present application, the temperature of the first etching is 20°C-35°C, so as to avoid the first etching solution from etching the second area due to excessively high temperature, thereby ensuring the texture etching effect of the glass body. Specifically, the first etching temperature may be, but is not limited to, 20°C, 22°C, 24°C, 26°C, 28°C, 30°C, 32°C or 35°C. In one embodiment of the present application, the temperature of the hydrofluoric acid may be 20°C-30°C. In another embodiment of the present application, the temperature of the hydrofluoric acid may be 25°C-35°C.
[0087] After the first etching, the haze and roughness of the glass body change, that is, the haze and roughness of the glass body are different from those of the glass substrate. In one embodiment of the present application, the haze of the glass body is 2%-3%, the roughness of the first surface of the glass body is less than or equal to 0.05μm, and the visible light transmittance of the glass body is 93%-99%. Specifically, the haze of the glass body can be but not limited to 2%, 2.2%, 2.4%, 2.6%, 2.8% or 3%, etc.; the roughness of the first surface of the glass body can be but not limited to less than or equal to 0.05μm, less than or equal to 0.045μm, less than or equal to 0.04μm, less than or equal to 0.03μm or less than or equal to 0.02μm, etc.; the visible light transmittance of the glass body can be but not limited to 93%, 94%, 95%, 96%, 98% or 99%, etc. In one embodiment of the present application, the haze of the glass body may be 2%-2.6%, the roughness of the first surface of the glass body may be less than or equal to 0.045 μm, and the visible light transmittance of the glass body may be 93%-96%. In another embodiment of the present application, the haze of the glass body may be 2.5%-3%, the roughness of the first surface of the glass body may be less than or equal to 0.03 μm, and the visible light transmittance of the glass body may be 95%-99%.
[0088] In one embodiment of the present application, the haze of the glass substrate is 5%-15%, the surface roughness of the glass substrate is 0.05μm-0.08μm, and the visible light transmittance of the glass substrate is 92%-93%. Specifically, the haze of the glass substrate after the first etching may be, but not limited to, 5%, 7%, 8%, 10%, 12%, 14% or 15%, etc.; the roughness of the glass substrate may be, but not limited to, 0.05μm, 0.055μm, 0.06μm, 0.065μm, 0.07μm, 0.075μm or 0.08μm, etc.; the visible light transmittance of the glass substrate may be, but not limited to, 92%, 92.2%, 92.4%, 92.6%, 92.8% or 93%, etc. Among them, the surface roughness of the glass substrate is the surface roughness of the surface on one side with the protrusion. In one embodiment of the present application, the haze of the glass substrate may be 5%-11%, the surface roughness of the glass substrate may be 0.05 μm-0.074 μm, and the visible light transmittance of the glass substrate may be 92%-92.6%. In another embodiment of the present application, the haze of the glass substrate may be 10%-15%, the surface roughness of the glass substrate may be 0.07 μm-0.08 μm, and the visible light transmittance of the glass substrate may be 92.5%-93%.
[0089] In the present application, the first area and the second area may be randomly distributed on the first surface. Specifically, the first area and the second area may be randomly and uniformly distributed on the first surface of the glass body. In one embodiment of the present application, the area ratio of the first area and the second area is 1:(2.3-4). Specifically, the area ratio of the first area and the second area may be, but is not limited to, 1:2.3, 1:2.5, 1:3, 1:3.2, 1:3.5, 1:3.8 or 1:4, etc. In one embodiment of the present application, the area ratio of the first area and the second area may be 1:(2.3-3). In another embodiment of the present application, the area ratio of the first area and the second area may be 1:(2.8-4). In some embodiments, the distribution of the first area and the second area is set according to the desired glass surface pattern. For example, when the pattern is a leather texture, the random distribution of the first area and the second area appears as a leather texture; when the pattern is a water ripple, the random distribution of the first area and the second area appears as a water ripple.
[0090] In the present application, a second etching solution is used to perform a second etching on the first region and the second region to obtain glass. Figure 1 , Figure 4 and Figure 5, a second etching liquid is used to perform a second etching on the first region 11 after the first etching and the second region 12 not subjected to the first etching; that is, the protrusions 23 and the second sub-surface 22 in the glass substrate 200 are subjected to a second etching to obtain a glass 300, wherein the glass 300 has a plurality of protrusion structures 33, and the side surfaces of the protrusion structures 33 are curved surfaces. Specifically, the glass 300 includes a first glass body 31 and a plurality of protrusion structures 33 disposed on a first sub-surface 32 of the first glass body 31, the first region 11 of the glass body 100 forms the second sub-surface 22 of the glass substrate 200 after the first etching, and the second sub-surface 22 of the glass substrate 200 forms the first sub-surface 32 of the first glass body 31 after the second etching; the protrusions 23 of the glass substrate 200 form the protrusion structures 33 after the second etching. Among them, the height of the glass body is equal to the height of the glass substrate, and the height of the glass substrate is greater than the height of the glass. After the second etching, the side and top surfaces of the protrusions are corroded by the second etching liquid, resulting in changes in the shape of the side and top surfaces of the protrusions. The horizontal side surfaces of the protrusions in the glass matrix are changed into arc-shaped side surfaces of the protrusion structure in the glass. There are no sharp corners in the protrusion structure, which reduces the stress concentration area when under pressure, avoids the pressure being concentrated at the connection between the side and top surfaces of the protrusions when under pressure, and causes glass breakage, thereby improving the strength of the glass, and further facilitating the improvement of the mechanical properties of the glass. At the same time, the defective part of the texture profile formed in the glass matrix after the first etching is subjected to the second etching to improve the good rate of the glass.
[0091] In one embodiment of the present application, the first surface of the glass body is composed of a first region and a second region, and the first region and the second region form glass after the first etching and the second etching. In another embodiment of the present application, the first surface of the glass body includes a first region, a second region, and a third region. That is, the first surface of the glass body still has an unetched region after the first etching and the second etching.
[0092] In one embodiment of the present application, the second etching solution includes but is not limited to at least one of ammonium salts, fluorides, fluorosilicates and inorganic acids. The combination of different components can form microscopic particles of different morphologies on the first surface and the second surface of the glass body, thereby producing a richer macroscopic visual effect. Specifically, the ammonium salt may include but is not limited to at least one of ammonium fluoride, ammonium bifluoride and ammonium chloride, the fluoride may include but is not limited to at least one of sodium fluoride, potassium fluoride and calcium fluoride, the fluorosilicate may include but is not limited to at least one of sodium fluorosilicate and potassium fluorosilicate, and the inorganic acid may include but is not limited to at least one of nitric acid, hydrochloric acid, sulfuric acid and hydrofluoric acid. In one embodiment of the present application, when the second etching solution includes calcium fluoride and hydrochloric acid, the microscopic morphology of the glass surface after etching is a tetrahedral shape. In one embodiment of the present application, when the second etching solution includes ammonium fluoride, ammonium bifluoride and nitric acid, the microscopic morphology of the glass surface after etching is a cube. In another embodiment of the present application, the second etching solution does not include an inorganic acid, and when the solvent is an aqueous solution, the remaining components dissolve in water to form hydrofluoric acid with etching ability, and the microscopic morphology of the glass surface after etching presents a plurality of spherical shapes. In some embodiments, the glass surface presents a leather texture visible to the naked eye, and the microscopic morphology of the glass surface presents a tetrahedral, cubic, or spherical shape. In some embodiments, the glass surface presents a water ripple visible to the naked eye, and the microscopic morphology of the glass surface presents a tetrahedral, cubic, or spherical shape.
[0093] In one embodiment of the present application, the second etching solution includes 15% ammonium bifluoride, 17% sodium fluoride, 5% calcium fluoride, 11% barium sulfate, and the remaining components are water, and the microscopic particles are spherical. In another embodiment of the present application, when the second etching solution includes ammonium fluoride, ammonium bifluoride and nitric acid, the microscopic particles are cubic.
[0094] In one embodiment of the present application, the second etching time is 30s-5min. Specifically, the second etching time may be, but is not limited to, 30s, 1min, 2min, 3min, 4min or 5min. In one embodiment of the present application, the second etching time may be 30s-4min. In another embodiment of the present application, the second etching time may be 3min-5min.
[0095] In one embodiment of the present application, the glass body includes a planar glass body and a curved glass body. In the related art, ultra-fine textures are etched on the surface of the curved glass body, especially on the edge arc surface. Usually, after the textures are etched on the planar glass body, the etched planar glass is hot-bent using a graphite mold to obtain curved glass. This process causes great damage to the graphite mold, increases the production cost of the product, and is not conducive to the widespread use of the product. In the present application, etching is directly performed on the curved glass body to avoid damage to the graphite mold and reduce the production cost of the glass. In one embodiment of the present application, after the glass raw material is cut using a diamond tool, a computer numerical control machine tool (CNC) or a laser is used to directly cut the glass raw material to obtain the glass body, and the glass body is hot-bent using a graphite mold to obtain the curved glass body.
[0096] In one embodiment of the present application, Figure 1 As shown, the glass body 100 is in a planar shape. Figure 6 , is a cross-sectional schematic diagram of a glass body provided in another embodiment of the present application, wherein the glass body 100 is in a curved shape, and the glass body 100 includes a main body 15 and an extension 16 disposed at the edge of the main body 15, the extension 16 is bent toward the main body 15, the main body 15 includes a third surface 151 and a fourth surface 152 disposed oppositely, the extension 16 includes a fifth surface 161 and a sixth surface 162 disposed oppositely, the third surface 151 and the fifth surface 161 are connected to form a first surface 10 of the glass body 100, and the fourth surface 152 and the sixth surface 162 are connected to form a second surface 13 of the glass body 100. In one embodiment of the present application, the third surface of the main body can be a curved surface or a flat surface, and the fourth surface can be a curved surface or a flat surface, so that the curved glass body has a variety of appearance effects.
[0097] See also Figure 7 , is a flow chart of a method for preparing glass provided in another embodiment of the present application, comprising:
[0098] S201: performing heat bending treatment on a glass precursor to obtain a curved glass body, wherein the glass body has a first surface and a second surface that are oppositely disposed, and the first surface has a first region and a second region;
[0099] S202: After performing a first etching on the first area, performing a second etching on the first area and the second area to obtain glass; the glass includes a first glass body and a plurality of protruding structures arranged on a first sub-surface of the first glass body, the protruding structures have a side surface, the side surface is a curved surface, and an angle between the first sub-surface and the side surface is an acute angle.
[0100] In one embodiment of the present application, the temperature of the heat bending treatment is 600°C-800°C, and the time of the heat bending treatment is 30s-60s. Specifically, the temperature of the heat bending treatment may be, but not limited to, 600°C, 650°C, 700°C, 750°C, 780°C or 800°C, etc.; the time of the heat bending treatment may be, but not limited to, 30s, 35s, 40s, 45s, 50s, 55s or 60s, etc. In one embodiment of the present application, the temperature of the heat bending treatment may be 700°C, and the time of the heat bending treatment may be 50s. In one embodiment of the present application, the heat bending treatment may include heating and softening a glass precursor in a mold to obtain a curved glass body.
[0101] In one embodiment of the present application, the glass body is pre-treated before the first etching. In one embodiment of the present application, the pre-treatment includes cleaning the glass body with an alkaline cleaning solution, the pH value of the alkaline cleaning solution is 9-11, which can remove excess impurities on the surface of the glass body and improve the cleanliness of the glass. Specifically, the pH value of the alkaline cleaning solution can be, but is not limited to, 9, 9.5, 10, 10.5 or 11. In one embodiment of the present application, the pH value of the alkaline cleaning solution can be 9-10.5. In another embodiment of the present application, the pH value of the alkaline cleaning solution can be 10-11.
[0102] In one embodiment of the present application, the concentration of the alkaline cleaning solution is 5%-7%, which can improve the cleanliness of the surface of the glass body. Specifically, the concentration of the alkaline cleaning solution can be, but is not limited to, 5%, 5.5%, 5.7%, 5.9%, 6%, 6.2%, 6.5%, 6.7% or 7%. In one embodiment of the present application, the concentration of the alkaline cleaning solution can be 5%-6.4%. In another embodiment of the present application, the concentration of the alkaline cleaning solution can be 6%-7%.
[0103] In one embodiment of the present application, the cleaning temperature is 50°C-60°C, and the cleaning time is 15min-20min. Specifically, the cleaning temperature may be, but not limited to, 50°C, 51°C, 52°C, 55°C, 57°C, 59°C or 60°C, etc.; the cleaning time may be, but not limited to, 15min, 13min, 17min, 18min, 19min or 20min, etc. In one embodiment of the present application, the cleaning time may be 50°C-56°C, and the cleaning time may be 15min-18min. In another embodiment of the present application, the cleaning time may be 54°C-60°C, and the cleaning time may be 17min-20min.
[0104] In one embodiment of the present application, a continuous ultrasonic cleaning line is used to clean the glass body, and drying is also included. The drying temperature is 120°C-150°C to ensure that the surface water content of the glass body is low, which is beneficial to the subsequent ink spraying and photoresist spraying, and improves the bonding ability of the ink and photoresist with the glass body. Specifically, the drying temperature can be but is not limited to 120°C, 125°C, 130°C, 135°C, 140°C, 145°C or 150°C, etc. In one embodiment of the present application, the drying temperature can be 120°C-135°C. In another embodiment of the present application, the drying temperature can be 132°C-150°C.
[0105] See also Figure 8 , which is a flow chart of a method for preparing glass provided in another embodiment of the present application, comprising:
[0106] S301: providing a glass body, wherein the glass body has a first surface and a second surface arranged opposite to each other, and the first surface has a first area and a second area;
[0107] S302: disposing a photoresist layer on the first surface, exposing and developing the photoresist layer to expose the first area;
[0108] S303: After performing a first etching on the first area, performing a second etching on the first area and the second area to obtain glass; the glass includes a first glass body and a plurality of protruding structures arranged on a first sub-surface of the first glass body, the protruding structures have a side surface, the side surface is a curved surface, and an angle between the first sub-surface and the side surface is an acute angle.
[0109] In one embodiment of the present application, spraying is performed on the first surface to obtain a photoresist layer, wherein the number of spraying is 2 to 4 times, and multiple spraying can improve the uniformity of the photoresist layer. In one embodiment of the present application, when the glass body is a curved glass body, spraying is required twice: the first time is to spray the entire surface without distinction, and the second time is to set the program to spray the curved curvature part, thereby ensuring the thickness consistency of the photoresist layer, which is conducive to the subsequent etching.
[0110] In one embodiment of the present application, the thickness of the photoresist layer is 3μm-6μm, which is conducive to subsequent texture drawing. Specifically, the thickness of the photoresist layer is 3μm-6μm. Specifically, the thickness of the photoresist layer can be but is not limited to 3μm, 3.4μm, 3.8μm, 4μm, 4.2μm, 4.6μm, 4.8μm, 5μm, 5.5μm or 6μm, etc. In one embodiment of the present application, the thickness of the photoresist layer can be 3μm-5.1μm. In another embodiment of the present application, the thickness of the photoresist layer can be 4.5μm-6μm.
[0111] In one embodiment of the present application, the main component of the photoresist layer includes linear phenolic resin and heavy naphthoquinone sensitizer, wherein the molecular weight of the linear phenolic resin is 30000-50000. Specifically, the molecular weight of the linear phenolic resin can be but not limited to 30000, 32000, 35000, 38000, 40000, 44000, 45000, 46000, 48000 or 50000 etc. In one embodiment of the present application, the molecular weight of the linear phenolic resin can be 30000-42000. In another embodiment of the present application, the molecular weight of the linear phenolic resin can be 40000-50000.
[0112] In one embodiment of the present application, after the photoresist layer is set, the first surface is surface dried, the surface drying temperature is 90°C-105°C, and the surface drying time is 5min-10min. Specifically, the surface drying temperature may be, but not limited to, 90°C, 92°C, 95°C, 98°C, 100°C, 102°C or 105°C, etc.; the surface drying temperature may be, but not limited to, 5min, 6min, 7min, 8min, 9min or 10min, etc. In one embodiment of the present application, the surface drying temperature may be 90°C-100°C, and the surface drying time may be 5min-8min. In another embodiment of the present application, the surface drying temperature may be 98°C-105°C, and the surface drying time may be 7min-10min. In some embodiments, the surface is dried by tunnel furnace drying, and the tunnel furnace is heated by a hot plate to ensure the uniformity of the temperature and increase the speed of surface drying.
[0113] In one embodiment of the present application, the photoresist layer is exposed and developed, and the pre-drawn texture drawing is input into the exposure machine, and the dot matrix laser (ultraviolet light) irradiates and exposes the exposure area according to the texture drawing. Specifically, the photoresist includes at least one of a positive photoresist and a negative photoresist. In one embodiment of the present application, a positive photoresist is used to form an exposure area and a non-exposure area on the first surface of the glass body, the exposure area is the first area, and the non-exposure area is the second area, and the first area and the second area constitute the patterned texture of the glass. In some embodiments, an exposure machine such as a laser direct writing exposure machine (LDI) with a laser angle adjustment function is required. For a curved glass body, the exposure angle can be adjusted for the curved curvature area, which is beneficial to improve the texture clarity of the curved area.
[0114] In one embodiment of the present application, the exposure energy is 600 mj / cm 2 -1000mj / cm 2 Specifically, the exposure energy may be, but is not limited to, 600 mj / cm 2 、700mj / cm 2 、750mj / cm 2、800mj / cm 2 、850mj / cm 2 、900mj / cm 2 、950mj / cm 2 or 1000mj / cm 2 In one embodiment of the present application, the exposure energy may be 600 mj / cm 2 -850mj / cm 2 In another embodiment of the present application, the exposure energy may be 750 mj / cm 2 -1000mj / cm 2 .
[0115] In one embodiment of the present application, the photoresist in the exposure area is cleaned by a horizontal developing line to facilitate the subsequent first etching. The first area after exposure is developed using a developer, and the developer can be but is not limited to at least one of a sodium hydroxide solution and a potassium hydroxide solution, the concentration of the developer is 0.8%-1.2%, and the development time is 1min-2min. Specifically, the concentration of the developer can be but is not limited to 0.8%, 0.85%, 0.9%, 1%, 1.05%, 1.1%, 1.15% or 1.2%, etc., and the development time can be but is limited to 1min, 1.2min, 1.5min, 1.8min, 1.9min or 2min, etc. In one embodiment of the present application, the developer can be a sodium hydroxide solution, the concentration can be 0.8%-1%, and the development time can be 1min-1.6min. In another embodiment of the present application, the developer can be a potassium hydroxide solution, the concentration can be 0.95%-1.2%, and the development time can be 1.2min-2min.
[0116] In one embodiment of the present application, baking is further performed after development, and the baking temperature is 150°C-170°C, and the baking time is 20min-40min. Specifically, the baking temperature may be, but not limited to, 150°C, 155°C, 160°C, 165°C or 170°C, etc.; the baking time may be, but not limited to, 20min, 25min, 28min, 30min, 35min, 38min or 40min, etc. In one embodiment of the present application, the baking temperature may be 150°C-167°C, and the baking time may be 20min-34min. In another embodiment of the present application, the baking temperature may be 160°C-170°C, and the baking time may be 30min-40min.
[0117] In one embodiment of the present application, before the first etching, a protective layer can be provided on the second surface to prevent the second surface of the glass body from being corroded by the etching solution during the subsequent etching process, thereby destroying the smoothness and flatness of the glass body. The thickness of the protective layer is 30μm-40μm, which improves the flatness of the glass body. Specifically, the thickness of the protective layer can be but is not limited to 30μm, 32μm, 34μm, 36μm, 38μm or 40μm, etc. In one embodiment of the present application, the thickness of the protective layer can be 30μm-38μm. In another embodiment of the present application, the thickness of the protective layer can be 35μm-40μm.
[0118] In one embodiment of the present application, after the second etching, the protective layer on the second surface of the glass body is removed, and then the glass body is ultrasonically cleaned to remove residual impurities. In some embodiments, the material of the protective layer is ink. In one embodiment of the present application, after the second etching, a tempering treatment is also included, and the glass body can be tempered to improve the mechanical strength of the glass, which is beneficial to the further application of the glass. Specifically, the tempering treatment may include but is not limited to at least one of a physical tempering treatment and a chemical tempering treatment. Exemplarily, the physical tempering treatment heats the glass body to a suitable temperature and then cools it, causing the surface of the glass body to shrink, generating compressive stress, and generating tensile stress inside the glass body, thereby improving the mechanical properties of the glass; the chemical tempering treatment improves the compressive stress on the surface of the glass body by improving the surface components of the glass body, thereby improving the mechanical strength of the glass. In one embodiment of the present application, a physical tempering treatment is used to temper the glass body.
[0119] The present application provides a glass cover plate, including the glass described in any one of the above embodiments. Due to the fine texture and excellent mechanical properties of the glass, the glass cover plate has high overall strength, diversified textures, low preparation cost, and strong product competitiveness. Fig. 9, is a cross-sectional schematic diagram of a glass cover provided in one embodiment of the present application, wherein the glass cover 400 includes a glass 300 and a decorative layer 41 disposed on the surface of the glass 300, which can further improve the appearance of the glass cover. Specifically, the decorative layer may include, but is not limited to, at least one of a color layer, a texture layer, and an optical film layer. Exemplarily, the color of the decorative layer of the color layer may be, but is not limited to, black, white, and red, etc.; the material of the color layer may be, but is not limited to, polyester film (PET); the texture layer may be, but is not limited to, at least one of a patterned texture, a matte texture, and a gradient texture; the optical film layer may be, but is not limited to, at least one of a titanium oxide coating layer, a silicon oxide coating layer, and a zirconium oxide coating layer. In some embodiments, when the decorative layer includes more than two different film layers, there is no restriction on the number and order of stacking of different film layers. The material, quantity, position, and stacking order of each film layer may be selected according to the appearance requirements of the glass cover. In one embodiment of the present application, a decorative layer is disposed on the side away from the glass having a convex structure surface, and the decorative layer may be a black color layer, so that the glass presents a black leather effect.
[0120] The present application also provides an electronic device, including the glass cover plate described in any of the above embodiments. Due to the diversified textures and good mechanical properties of the glass cover plate, the appearance of the electronic device has more options, the overall strength is increased, and the impact resistance is enhanced, which is conducive to the wide application of electronic devices. Specifically, the electronic device can be, but is not limited to, a mobile phone, a tablet computer, a laptop computer, a smart bracelet, an e-reader, etc. In one embodiment of the present application, the electronic device can be a mobile phone, which improves the appearance and practicality of the mobile phone and improves the anti-fall ability of the mobile phone.
[0121] The effect of the technical solution of the present application is further illustrated below through specific examples.
[0122] Example 1
[0123] A glass body is obtained by laser cutting, and a curved glass body is obtained by heat bending; the curved glass body is cleaned, ink is sprayed on the second surface, and the ink thickness is 35 μm; a photoresist is sprayed on the first surface by a vertical spraying machine, and the thickness of the photoresist layer is 3 μm; the surface drying temperature is 90° C., and the surface drying time is 10 minutes;
[0124] Using laser direct writing exposure machine at 600mj / cm 2 The exposed film was exposed at an exposure energy of , developed with a developer (potassium hydroxide with a concentration of 0.8%) for 1.5 min, and then baked at 150°C for 30 min;
[0125] A glass substrate is obtained after a first etching is performed using a first etching solution (hydrofluoric acid with a concentration of 3%), the first etching time is 3 minutes, the first etching temperature is 25° C., the photoresist layer on the first surface is removed, and a second etching solution (comprising 15% ammonium bifluoride, 17% sodium fluoride, 5% calcium fluoride, 11% barium sulfate, and the remaining components are water, by mass percentage) is used for a second etching, and the second etching time is 50 seconds.
[0126] The ink layer on the second surface is removed, the etched glass body is tempered, and a decorative layer (the decorative layer is made of a PET film and is black in color) is provided to obtain glass.
[0127] The glass body after the first etching, the glass body after the second etching, and the glass were tested using a Leica DM2700 crystal phase microscope. Fig.10 , Fig.11 and Fig.12 . Fig.10 This is a surface morphology image of the glass substrate obtained in Example 1 of the present application, magnified 20 times. Fig.11 This is a surface morphology image of the glass substrate obtained in Example 1 of the present application, magnified 5 times. Fig.12 This is a surface morphology image of the glass substrate obtained in Example 1 of the present application, magnified 50 times. Fig.13 This is a partial surface schematic diagram of the glass obtained in Example 1 of the present application. It can be seen that after the first etching, the glass substrate has a second sub-surface 22 and a protrusion 23, and after the second etching, the protrusion 23 is transformed into a protrusion structure 33. The side of the protrusion 23 is a horizontal plane, and after the second etching, the side of the protrusion structure 33 located on the first sub-surface 32 is a curved surface, which alleviates the stress concentration phenomenon and improves the mechanical strength of the glass. The surface morphology of the glass obtained in Example 1 is close to the texture of real leather.
[0128] Example 2
[0129] The difference from Example 1 is that the surface drying temperature is 100°C and the exposure energy is 900 mj / cm 2 , the developer is 1% sodium hydroxide. Fig.14 This is a partial surface schematic diagram of the glass prepared in Example 2 of the present application, in which the curved surface area has a clear leather texture.
[0130] Example 3
[0131] The difference from Example 1 is that the surface drying temperature is 105° C. and the depth of the first etching is 15 μm.
[0132] Example 4
[0133] The difference from Example 1 is that the exposure energy is 1000 mj / cm 2 .
[0134] Example 5
[0135] The difference from Example 1 is that the developer is sodium hydroxide with a concentration of 1.2%.
[0136] Example 6
[0137] The difference from Example 1 is that the first etching solution is hydrofluoric acid with a concentration of 1%.
[0138] Example 7
[0139] The difference from Example 1 is that the first etching solution is hydrofluoric acid with a concentration of 5%.
[0140] Example 8
[0141] The difference from Example 1 is that the first etching solution further includes 0.2% by mass of nitric acid and 0.2% by mass of sulfuric acid.
[0142] Example 9
[0143] The difference from Example 1 is that the first etching time is 5 minutes.
[0144] Example 10
[0145] The difference from Example 1 is that the first etching time is 15 minutes.
[0146] Embodiment 11
[0147] The difference from Example 1 is that the temperature of the first etching is 20°C.
[0148] Example 12
[0149] The difference from Example 1 is that the temperature of the first etching is 35°C.
[0150] Embodiment 13
[0151] The difference from Example 1 is that the second etching solution includes ammonium fluoride, ammonium bifluoride and nitric acid. Fig.15 This is a partial surface schematic diagram of the glass obtained in Example 13 of the present application, and the glass surface has water ripples.
[0152] Embodiment 14
[0153] The difference from Example 1 is that the second etching time is 90 seconds.
[0154] Comparative Example 1
[0155] The difference from Example 1 is that the second etching is not performed. Fig.16A partial surface schematic diagram of the glass prepared in Comparative Example 1 of the present application, wherein the flat surface and curved surface textures are unclear.
[0156] Comparative Example 2
[0157] The difference from Example 1 is that the first etching is not performed.
[0158] Performance Testing
[0159] The glasses obtained in the above-mentioned embodiments 1-14 and comparative examples 1-2 were divided into nine areas evenly according to a nine-square grid. Any side of each area after cutting was magnified 100 times by a crystal phase microscope, and the acute angle between the side of any protruding structure in the crystal phase micrograph and the first sub-surface was tested. The average value of the acute angle between the side of the protruding structure and the first sub-surface in the nine areas was taken as the acute angle between the side of the protruding structure of the glass and the first sub-surface. The results are shown in Table 1.
[0160] The haze of the glasses prepared in the above-mentioned Examples 1-14 and Comparative Examples 1-2 was tested according to ISO7027. The results are shown in Table 1.
[0161] The roughness of the glasses prepared in the above-mentioned Examples 1-14 and Comparative Examples 1-2 was tested according to GB / T32642-2016, and the results are shown in Table 1.
[0162] The glasses prepared in the above-mentioned Examples 1-14 and Comparative Examples 1-2 were tested for visible light transmittance according to GB / T7258-2017, and the results are shown in Table 1.
[0163] The glasses prepared in the above-mentioned Examples 1-14 and Comparative Examples 1-2 were tested for their flexural strength according to GB / T37781-2019. The test process was as follows: the glass was placed in a test fixture, the upper wheelbase of the fixture was set to 18 mm, the lower wheelbase was set to 36 mm, the loading rod diameter was set to 6 mm, and pressure was applied downward at a speed of 10 mm / min until the product broke. The test was repeated 10 times, and the average value of the maximum applied pressure was the flexural strength. The results are shown in Table 2.
[0164] The glasses prepared in the above-mentioned Examples 1-14 and Comparative Examples 1-2 were tested for their impact resistance according to GB / T2843-1981. The test process was as follows: the glass was placed in a steel ball drop tester, and a 65g steel ball was used to drop the glass from a height of 5cm. The drop height was gradually increased (such as 10cm, 15cm, 20cm, 25cm, etc.) until the glass was broken and failed. The results are shown in Table 2.
[0165] Table 1 Surface performance test results
[0166]
[0167]
[0168] Table 2 Mechanical properties test results
[0169] Bending strength(N) Impact resistance(cm) Example 1 422 55 Example 2 439 50 Example 3 412 45 Example 4 452 50 Example 5 437 50 Example 6 430 45 Example 7 457 55 Example 8 453 50 Example 9 450 50 Example 10 433 45 Embodiment 11 443 45 Example 12 431 45 Embodiment 13 465 45 Embodiment 14 430 45 Comparative Example 1 320 30 Comparative Example 2 411 35
[0170] According to Examples 1-14 and Comparative Examples 1-2, it can be seen that the side of the convex structure of the glass provided by the present application is a curved surface, and the angle between the side and the first sub-surface is an acute angle, which reduces the stress concentration area, improves the mechanical properties of the glass, and is conducive to promoting the wide application of the glass. According to Examples 1-14, it can be seen that the smaller the angle between the side and the first sub-surface, the higher the bending strength of the glass and the better the impact resistance; According to Examples 1 and 13, it can be seen that the difference in the second frosting liquid can change the haze, roughness and visible light transmittance of the glass, and the second frosting liquid can be regulated according to product requirements; According to Example 1 and Comparative Example 1, it can be seen that Comparative Example 1 does not perform the second etching, and the angle between the first sub-surface of the glass and the convex structure is a right angle, and the second etching etches the right angle into an acute angle, avoiding stress concentration, and improving the bending resistance and impact resistance of the glass; According to Examples 1 and Comparative Examples 1-2, it can be seen that performing the second etching can improve the mechanical properties of the glass, and the first etching can produce a convex structure with a height greater than the micron level on the glass surface, forming a macro texture. Therefore, the glass provided in the present application has excellent mechanical properties, which is conducive to the wide application of glass.
[0171] The above is a preferred embodiment of the present application, but it should not be understood as limiting the scope of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications are also considered to be within the scope of protection of the present application.
Claims
1. A glass, characterized in that: The glass comprises a first glass body and a plurality of protruding structures arranged on a first sub-surface of the first glass body, the protruding structures have a side surface, the side surface is a curved surface, and an angle between the first sub-surface and the side surface is an acute angle.
2. The glass according to claim 1, characterized in that The acute angle is 50°-80°.
3. The glass according to claim 1, characterized in that The orthographic projection area of the protruding structure on the first sub-surface accounts for 70%-80% of the area of the first sub-surface.
4. The glass according to claim 1, wherein The curvature of the side is 2m -1 -5m -1 .
5. The glass according to claim 1, wherein: The lateral dimension of the protruding structure is 0.1 mm-2.5 mm, the width of the protruding structure is 0.1 mm-1.5 mm, the height of the protruding structure is 0.1 μm-30 μm, and the spacing between adjacent protruding structures is 0.1 mm-0.2 mm.
6. The glass according to claim 5, characterized in that The lateral dimension of the protruding structure is 0.1 mm-1 mm, the width of the protruding structure is 0.1 mm-1 mm, the height of the protruding structure is 5 μm-15 μm, and the spacing between adjacent protruding structures is 0.1 mm-0.2 mm.
7. The glass according to claim 5, characterized in that The lateral dimension of the protruding structure is 1 mm-2.5 mm, the width of the protruding structure is 0.5 mm-1.0 mm, the height of the protruding structure is 10 μm-30 μm, and the spacing between adjacent protruding structures is 0.1 mm-0.13 mm.
8. The glass according to claim 1, wherein The haze of the glass is 40%-55%, the visible light transmittance of the glass is 60%-70%, and the surface roughness of the glass is 0.1 μm-0.3 μm.
9. The glass according to claim 1, wherein: The bending strength of the glass is greater than or equal to 430N, and the impact resistance height of the glass under the impact of a steel ball with a mass of 65g is greater than or equal to 45cm.
10. A method for preparing glass, characterized in that: include: Providing a glass body, wherein the glass body has a first surface and a second surface arranged opposite to each other, and the first surface has a first area and a second area; After the first area is etched for the first time, the first area and the second area are etched for the second time to obtain glass; the glass includes a first glass body and a plurality of protruding structures arranged on a first sub-surface of the first glass body, the protruding structures have a side surface, the side surface is a curved surface, and the angle between the first sub-surface and the side surface is an acute angle.
11. The preparation method according to claim 10, characterized in that: Using a first etching solution to perform the first etching, the first etching solution comprising hydrofluoric acid; The concentration of the hydrofluoric acid in the first etching solution is 1%-5%; The first etching time is 5 min-10 min.
12. The preparation method according to claim 10, characterized in that: The second etching is performed using a second etching solution, wherein the second etching solution includes at least one of an ammonium salt, a fluoride, a fluorosilicate, and an inorganic acid; The ammonium salt comprises at least one of ammonium fluoride, ammonium bifluoride and ammonium chloride; The fluoride comprises at least one of sodium fluoride, potassium fluoride and calcium fluoride; The fluorosilicate includes at least one of sodium fluorosilicate and potassium fluorosilicate; The inorganic acid includes at least one of nitric acid, hydrochloric acid, sulfuric acid and hydrofluoric acid.
13. The preparation method according to claim 10, characterized in that: Before performing the first etching, the method further comprises: Disposing a photoresist layer on the first surface; exposing and developing the photoresist layer to expose the first region; Wherein, the thickness of the photoresist layer is 3 μm-6 μm; The exposure energy is 600 mj / cm 2 -1000mj / cm 2 ; The developing is performed using a developer, wherein the developer comprises at least one of a potassium hydroxide solution and a sodium hydroxide solution, and the concentration of the developer is 0.8%-1.2%; The development time is 1 min-2 min.
14. The preparation method according to claim 10, characterized in that: Providing the glass body includes: performing heat bending treatment on a glass precursor to obtain the curved glass body.
15. A glass cover plate, comprising the glass according to any one of claims 1 to 9 or the glass prepared by the preparation method according to any one of claims 10 to 14.
16. The glass cover plate according to claim 15, characterized in that: The glass cover plate further comprises a decorative layer, and the decorative layer is arranged on the surface of the glass.
17. An electronic device, comprising the glass cover plate according to any one of claims 15 to 16.